Competency models in business students and business owners: a cross-national case study of Czechia and Romania - Duháček Šebestová, Jarmila; Kowala, Radek; Vodă, Ana Iolanda; Bercu, Ana-Maria (Business, Management and Economics Engineering, 2022)
Purpose – The main goal is to compare and contrast the expectations of millennials, which skills will be needed for business in contrast to the entrepreneurial experience of the focus group of eight successful entrepreneurs from each country.Research methodology – A cross-national case study is made, based on two focus groups per country (80 business students and eight entrepreneurs from the Czech Republic and Romania), qualitative research findings are presented.Findings – Two competency models were evaluated, when the Romanian model is mostly motivation-oriented and the Czech model is performance-oriented.Research limitations – Future studies should use an extended research sample and compare various methods for teaching entrepreneurship to students from different study areas and compare the impact of education on their mind-set before and after business courses finish.Practical implications – The development of competency models in cooperation with experienced entrepreneurs would have the potential to increase students’ willingness to start up and prepare tailored business education. Possibility to create own generic models.Originality/Value – The originality could be seen in comparison of two focus groups – students and entrepreneurs – which have not been done before from a conflict comparison point of view.